THE RELATIONSHIP OF THE MOTHER’S ROLE WITH THE HABIT OF WASHING HAND SOAP IN PRE-SCHOOL CHILDREN IN KINDERGARTEN WITH DHARMA WANITA SURU VILLAGE NGETOS SUB DISTRICT OF NGANJUK DISTRICT - Rupi'ah; Siti Farida Noor Laila; M. Ali Sodik (Universitas STRADA Indonesia, 2019)
Pre-school children are am early age where children before stepping on school.this period unfolds childhood 3-5 years old at this time the child uses his biological functions to determine various things in his world, children like to play in a very close position to each other, using their mouths,eating and blowing their conditions can have an impact on the high incidence of infection in pre-school children because of the easy spread of some infectious diseases through the hands.The purpose of this study was to determine the relashionship of the role of mother with the habit of washing hands with soap in pre-school childrennin kindergarten Dharma Wanita in Suru village Ngetos sub district of nganjuk district. the research design used in this descriptive analytic and cross-sectional methods. the number of mothers samples was 32 people data collaction using a questionnaire.Data analysis with sparman rho test. The results of the research on the role of mothers are known to be good, namely 21 respondents (66%), 9 respondents (28%) and less 2 respondents (6%).the habit of washing hands with soap is well known to 14 respondents(44%) , only 16 respondents (50%) and less than 2 respondents (6%).the habit of washing hands with soap is well known to 14 respondents(44%) , only 16 respondents (50%) and less than 2 respondents (6%).spearman rho test results obtained p= value 0.000 with α : 0.05 p value < α (0.000<0.05) which means that HO is rejected H1 is accepted then it can found that there is relationship. the conclusion of the research is that there is a relationship between the role of mother with the habit of washing hands with soap in pre-school childrennin kindergarten Dharma Wanita in Suru village Ngetos sub district of nganjuk district.Mothers should often follow counseling about clean and healthy living done by health workers so that it can be input for mothers understand the importance of washing hands with soap to prevent di sease.